2017
DOI: 10.3390/nu9050451
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Role of Atractylenolide-I in an In Vitro and In Vivo Model of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is an age-related neurological disorder characterized by a loss of dopaminergic neurons within the midbrain. Neuroinflammation has been nominated as one of the key pathogenic features of PD. Recently, the inadequate pharmacotherapy and adverse effects of conventional drugs have spurred the development of unconventional medications in the treatment of PD. The purpose of this study is to investigate the anti-neuroinflammatory mechanisms of Atractylenolide-I (ATR-I) in in vivo and in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…This has been proved both in cell cultures and in animal models treated with different natural compounds able to activate Nrf2/HO-1 reducing LPS-induced pro-inflammatory activation [91,92,93] and also reducing oxidative damage [94,95]. …”
Section: Ho-1 Protective Effects In Nervous Systemmentioning
confidence: 99%
“…This has been proved both in cell cultures and in animal models treated with different natural compounds able to activate Nrf2/HO-1 reducing LPS-induced pro-inflammatory activation [91,92,93] and also reducing oxidative damage [94,95]. …”
Section: Ho-1 Protective Effects In Nervous Systemmentioning
confidence: 99%
“…Parkinson's disease (PD) is considered a progressive neurodegenerative disorder characterized by the dopaminergic neuron loss in the substantia nigra pars compacta (SNpc) and neuroinflammation through microglial malfunction [ 92 , 93 ]. TQ exhibits protective activities in PD models.…”
Section: Neuropharmacological Potential Of Thymoquinonementioning
confidence: 99%
“…Pharmacokinetic studies in rats have demonstrated that, after oral administration, AT-I is readily absorbed and persists for extended periods of time, suggesting good oral bioavailability (Wang et al, 2008). AT-I has a wide range of biological and pharmacological properties, including neuroprotective, antiallergic, anti-inflammatory, and anti-cancer activities (Wang et al, 2009;Lim et al, 2012;More and Choi, 2017;Xiao et al, 2018). Previous studies have shown that AT-I is beneficial in treating various cancers through the regulation of different molecules and pathways.…”
Section: Introductionmentioning
confidence: 99%